Gastrointestinal amyloidosis occurring in three different patterns: Case serie - Riza Caliskan, Ali; Furkan Cagin, Yasir; Bilgic, Yilmaz; Yildirim, Oguzhan; Ali Erdogan, Mehmet; Seckin, Yuksel; Alan, Saadet; Karadag Soylu, Nese (Annals of Medical Research, 2021)
None
Keywords: Amyloidosis; Gastrointestinal System; Liver; Cholestasis; Diarrhea.br /